Comparative study of the particle morphology changes in copper powder using various media mills. Issue 3 (4th May 2017) - Amgalan, B.; Shiori, S.; Ichinkhorloo, B.; Uyanga, B.; Lee, Jehyun; Ochirkhuyag, B.; Choi, H.
Abstract: An experimental investigation has been conducted on grinding of copper powders using different ball-milling machines. A various parameters including rotation speed and grinding time and ball sizes are used to change the particle morphology of the copper powders. The effects of the ball mill operation condition on the morphology of Cu powders in the dry-type milling process using three different types of ball mill: traditional ball mill (TBM), stirred ball mill (SBM), and planetary ball mill (PBM). A new evaluation method, which can provide relatively accurate results, is used to analyze and compare the grinding performance of three different ball millings. The experimental results suggest that the particle size and morphology of copper particle can easily be controlled by changing grinding conditions of these ball millings. The results were systematically analyzed using scanning electron microscopy (SEM) and particle size analyzer (PSA).